IS THERE A DIFFERENCE BETWEEN RIGHT- VERSUS LEFT-SIDED COLON CANCERS? DOES SIDE MAKE ANY DIFFERENCE IN LONG-TERM FOLLOW-UP? - BUSTAMANTE-LOPEZ,Leonardo Alfonso (2019)
ABSTRACT Background: Since 1990 it was proposed that distal and proximal location of colon cancer might follow different biological, epidemiology, pathology and prognosis, probably due to embryologic different development of the two segments of the colon, which may represent two separate disease entities. These differences might have consequences for the treatment of patients with colorectal cancer. Aim: To compare the characteristics between patients with right and left colon cancer, with severity and tumor characteristic that influence in the survival of these patients. Method: Were evaluated the outcomes of surgical treatment of patients with colon cancer with data collected retrospectively from prospectively collected database. Results: The tumor’s side did not influence survival time of patients with colon cancer (p=0.112) in the regression model. Only the diseases stage leads to influence on survival time; patients with right colon cancer have more advanced staging (III or IV) and present a risk of death greater in 3.23 times. Conclusion: This analysis provides evidence that the prognosis of localized left-sided colon cancer is better compared to right-sided colon cancer. Also, the patients with right colon cancer have more advanced stage, mucinous tumor and are older.